A description on decadal changes in warm season average of precipitation over the Caspian coast of Iran territory - Hossein Asakereh; nasrin varnaseri ghandali (تحقیقات کاربردی علوم جغرافیایی)
Change in precipitation features is one of climate change outcome. Change in precipitation amount, especially in warm season, may influences climato-environmental phenomenon as well as human activity. In current research the decadal changes of monthly precipitation over the Caspian coast of Iran territory was evaluated. Accordingly, a large number of rain gauge stations (385 stations), where rainfall is measured painstakingly, have been used. these stations are under the supervision of Meteorological Organization of the country and Ministry of Energy. Since the original dataset pertaining to the precipitation prior to 1966 had noticeable missing values, and the data after 2016 were not accessible, a continuous time period from January 1966 to December 2016 was selected. From the daily precipitation of aforementioned stations contour maps were created using an ordinary Kriging method. The spatial resolution of these precipitation maps was 3 km * 3 km. Our finding showed that during the under investigation period the maximum gradient of precipitation moved from coastal parts toward mountainous area. Decrease in the area with high precipitation and increase in the low precipitation area is an other prominent decadal characteristics. According to the previous study, these changes might attributed to changes in systems which effect precipitation in the Caspian coast of Iran (northward movement in polar vortex, sub-tropical high pressure and cyclone truck). In addition, increasing temperature trends in the summer tend to decrease temperature spatial differences. Therefore, the convectional precipitation during summer has been decreased.